Investigation of Dynamic Spillovers of Foreign Direct Investment and Human Capital in Pakistan - Yasmin, Fouzia; Safdar, Noreen; Shah , Salyha Zulfiqar Ali (Pakistan Journal of Humanities and Social Sciences, 2022)
Human capital enhancement is a leading indicator for sustainable development, and it has proven as a significant and widespread area of research over a few decades ago. In addition, emerging states’ FDI consequently enhances the human capital comparatively with its previous level. Empirically, this research explains the association between foreign direct investment and human capital in Pakistan. Annual time series data is obtained for 1976 to 2020. ARDL is applied to the analysis and estimates the effect of many-core variables on human capital. The econometric analysis reveals unidirectional running from foreign direct investment to human capital. Therefore, foreign direct investment is not satisfactory and sufficient to bring Pakistan back to growth along with this; however, the other variables as the trade opens are essential to consider.